National health insurance policy in Nepal: challenges for implementation - Shiva Raj Mishra; Pratik Khanal; Deepak Kumar Karki; Per Kallestrup; Ulrika Enemark (Taylor & Francis Group, 2015)
The health system in Nepal is characterized by a wide network of health facilities and community workers and volunteers. Nepal's Interim Constitution of 2007 addresses health as a fundamental right, stating that every citizen has the right to basic health services free of cost. But the reality is a far cry. Only 61.8% of the Nepalese households have access to health facilities within 30 min, with significant urban (85.9%) and rural (59%) discrepancy. Addressing barriers to health services needs urgent interventions at the population level. Recently (February 2015), the Government of Nepal formed a Social Health Security Development Committee as a legal framework to start implementing a social health security scheme (SHS) after the National Health Insurance Policy came out in 2013. The program has aimed to increase the access of health services to the poor and the marginalized, and people in hard to reach areas of the country, though challenges remain with financing. Several aspects should be considered in design, learning from earlier community-based health insurance schemes that suffered from low enrollment and retention of members as well as from a pro-rich bias. Mechanisms should be built for monitoring unfair pricing and unaffordable copayments, and an overall benefit package be crafted to include coverage of major health services including non-communicable diseases. Regulations should include such issues as accreditation mechanisms for private providers. Health system strengthening should move along with the roll-out of SHS. Improving the efficiency of hospital, motivating the health workers, and using appropriate technology can improve the quality of health services. Also, as currently a constitution drafting is being finalized, careful planning and deliberation is necessary about what insurance structure may suit the proposed future federal structure in Nepal.